The Rewriting of Myth: Reactualization of Cultural Elements, the Formation of a Writing Style, and the Assertion of Singularity - Tebani, Ibtissam (El Omda in Linguistics and Discourse Analysis, 2023)
The rewriting of myth is a theme that has been widely examined in scholarly discourse, with the primary aim of explaining the role of myth in preserving cultural identity and shaping the collective unconscious of a community. In this article, we seek to demonstrate how the rewriting of myths by Maghrebi writers contributes to the preservation of cultural heritage while simultaneously fostering the development of individual writing styles. This is achieved through the reactualization of the myth of El Kahina—a historical figure and Berber princess—in the works of the Algerian writer Kateb Yacine and the Moroccan writer Mohammed Khaïr-Eddine.